Unveiling the Gender Gap: A Literature Review on Women Entrepreneurs and Financial Access - Ni Made Sri Rukmiyati; Ni Wayan Noviana Safitri; Ni Ketut Mareni; Ni Putu Ayu Darmayanti; Ni Nengah Seri Ekayani (Universitas Warmadewa, 2024)
This study conducts a systematic literature review to examine the current state of research on access to finance for women entrepreneurs. The review reveals the multifaceted nature of factors influencing gender disparities in financial access and their consequent business performance. While some scholars debate the role of gender discrimination versus differences in motivations and preferences between male and female entrepreneurs, empirical evidence suggests that disparities persist, albeit with variations across regions. Notably, studies highlight differences in loan sizes between women and men, indicating nuanced challenges faced by women in accessing formal finance. Furthermore, contextual factors such as the level of financial development, institutional norms, gender behavior, and individual perceptions shaped by stereotypes contribute to these disparities. Policy initiatives promoting gender equality in financial access and fostering an inclusive business environment emerge as crucial strategies to address these challenges and harness the potential of women entrepreneurs for economic development. This study provides a comprehensive foundation for further research into the determinants of women entrepreneurs' financial access and informs the design of targeted policy interventions aimed at mitigating gender disparities in entrepreneurship.